2019
DOI: 10.1111/iej.13255
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus reactivation by persistent apical periodontal pathogens

Abstract: Aim To assess whether Epstein–Barr virus (EBV) reactivation is triggered by persistent apical periodontitis‐related microbes using in vitro and ex vivo methodologies. Methodology Surgically removed human periapical granulomas (n = 50) and healthy gingival tissues (n = 10) were analysed to determine the presence of EBV and seven persistent apical periodontitis‐related microbes. In addition, real‐time polymerase chain reaction was used to detect the mRNA expression of BZLF‐1, an immediate–early gene of EBV. Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…In this regard, EBV was recently suggested to be involved in the pathogenesis of other chronic inflammatory infections occurring in the periodontium such as peri-implantitis and periapical periodontitis [50][51][52]. In contrast with unexplained peri-implantitis, some interesting mechanisms are reported with periapical periodontitis, i.e., BA excreted by P. endodontalis and F. nucleatum in addition to EBV is involved in the progression of periapical periodontitis [53,54]. An underlying mechanism may involve reactive oxygen species released from EBV-infected host cells that induce local imbalance between receptor activator NF-κB and osteoprotegerin, which consequently promotes alveolar bone resorption [55].…”
Section: Etiological Significances Of Ebv Infection In the Periodontiummentioning
confidence: 99%
“…In this regard, EBV was recently suggested to be involved in the pathogenesis of other chronic inflammatory infections occurring in the periodontium such as peri-implantitis and periapical periodontitis [50][51][52]. In contrast with unexplained peri-implantitis, some interesting mechanisms are reported with periapical periodontitis, i.e., BA excreted by P. endodontalis and F. nucleatum in addition to EBV is involved in the progression of periapical periodontitis [53,54]. An underlying mechanism may involve reactive oxygen species released from EBV-infected host cells that induce local imbalance between receptor activator NF-κB and osteoprotegerin, which consequently promotes alveolar bone resorption [55].…”
Section: Etiological Significances Of Ebv Infection In the Periodontiummentioning
confidence: 99%
“…Last but not least, it is a well-known fact that production of butyrate is an important virulence for F. nucleatum. F. nucelatum utilizes amino acids such as glutamate, lysine, and fructose as an energy source and produce SCFAs including butyrate (Himi et al, 2020;Llama-Palacios et al, 2020). Although we didn't identify relevant DEGs in F. nucelatum subsp.…”
Section: S Gordonii Degs Associated With the Pyruvate Metabolism And Peptidoglycan Biosynthesis Were Affected Following Coaggregationmentioning
confidence: 76%
“…It is reported that P. gingivalis and F. nucleatum can take part in the regulation of acetylation and deacetylase for histone, thus reactivating the EBV by modulating the BZLF1 promoter in EBV-infected cells ( Imai et al., 2012a ; Imai et al., 2012c ). Butyrate (BA), which belongs to a short-chain fatty acid (SCFA) family ( Louis et al., 2010 ; Imai et al., 2012b ), was reported to be excreted by P. endodontalis and F. nucleatum in EBV carriers, and leads to the occurrences of periapical periodontitis ( Makino et al., 2018 ; Himi et al., 2020 ). In addition, studies have also declared that the intraperitoneal injection of BA in EBV-driven cancers accelerates the expression of ZEBRA expression and reactivate the lytic EBV replication ( Westphal et al., 1999 ; Westphal et al., 2000 ).…”
Section: Other Commensal Microbiome Could Interact With Ebv In Ebv-dr...mentioning
confidence: 99%